ANALISIS PENGARUH KEPERCAYAAN MASYARAKAT PADA PAJAK TERHADAP KEPATUHAN PAJAK DIMODERASI OLEH KEKUATAN OTORISASI PAJAK PEMERINTAH: STUDI KASUS PADA MAHASISWA DI KOTA BATAM - Vionita, Vinny; Ria Karina (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
This study aims to determine the effect of trust and power variables on tax compliance. The dependent variable in this study is voluntary tax compliance and forced tax compliance. Trust as an independent variable and power as a moderating variable. The control variables in this study were age, education, gender. The survey was conducted by giving a questionnaire. Respondents who were used as samples were all students in Batam City. The questionnaire consists of 12 questions which are measured using a Likert scale. After collecting the respondents' results, the authors used SPSS software to test the data. From the test results it can be concluded that there are several variables that the authors examine have a significant influence. The results showed that the trust variable had a significant positive effect on voluntary tax compliance, then had a significant negative effect on taxpayer compliance. After including the interaction variable between trust and strength, it was found that the strength variable did not strengthen the effect of the trust relationship on voluntary tax compliance and enforced tax compliance.